Juventude e religiosidade: como os jovens se relacionam com o transcendente, a moral e a educação - Meneguce, Anderson Pimentel (2009)
An analysis of the religiosity of the young peoples in IPB. The first part covers the early adulthood, psychosocial aspects, cognitive, moral and their faith, from the theories of development. The second part brings a social research with young people to identify the stages where they are and identify their needs in the context of faith and morals. The third and last part, seeks to offer grants a christian form of religious education for youths from the characteristics of young adulthood and the challenges and anxieties that this stage of life provides for humans. The Christian religious education to young adulthood in the Presbyterian Church of Brazil should be a safe and protected, where young people might question their faith, their morals, their existence and their religious group. The answers to these questions should not sound like truths sacred, immutable, but indicate the way for a meeting with the reflective True and Living God and to embrace a morality of universal principles. Thus, the couple is ready to mature, to exercise a role in search for a fairer society and have the ability to reflect critically on their identity and their ideologies.